The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.4049/jimmunol.173.7.4452
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Acid Sphingomyelinase and Its Inhibition by the Nitric Oxide/Cyclic Guanosine 3′,5′-Monophosphate Pathway: Key Events in Escherichia coli-Elicited Apoptosis of Dendritic Cells

Abstract: Depletion of dendritic cells (DCs) via apoptosis contributes to sepsis-induced immune suppression. The mechanisms leading to DC apoptosis during sepsis are not known. In this study we report that immature DCs undergo apoptosis when treated with high numbers of Escherichia coli. This effect was mimicked by high concentrations of LPS. Apoptosis was accompanied by generation of ceramide through activation of acid sphingomyelinase (A-SMase), was prevented by inhibitors of this enzyme, and was restored by exogenous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
89
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(92 citation statements)
references
References 83 publications
(73 reference statements)
3
89
0
Order By: Relevance
“…The use of genetically altered cells or pharmacological inhibitors proved the importance of the acid sphingomyelinase/ ceramide system in the infection of mammalian cells by these pathogens. Consistent with the general function of ceramide in the signaling processes described above, the acid sphingomyelinase/ceramide system has been shown to be involved in several effects induced by the pathogens, including uptake/invasion of the pathogen, induction of apoptosis in the infected mammalian host cell, and regulation of the cellular and humoral immune responses (Grassmé et al, 1997(Grassmé et al, , 2003a(Grassmé et al, , 2005Hauck et al, 2000;Esen et al, 2001;Pfeiffer et al, 2001;Utermöhlen et al, 2003;Falcone et al, 2004;McCollister et al, 2007;Utermöhlen et al, 2008;Simonis et al, 2014).…”
Section: Ceramide In Bacterial Infectionsmentioning
confidence: 86%
See 2 more Smart Citations
“…The use of genetically altered cells or pharmacological inhibitors proved the importance of the acid sphingomyelinase/ ceramide system in the infection of mammalian cells by these pathogens. Consistent with the general function of ceramide in the signaling processes described above, the acid sphingomyelinase/ceramide system has been shown to be involved in several effects induced by the pathogens, including uptake/invasion of the pathogen, induction of apoptosis in the infected mammalian host cell, and regulation of the cellular and humoral immune responses (Grassmé et al, 1997(Grassmé et al, , 2003a(Grassmé et al, , 2005Hauck et al, 2000;Esen et al, 2001;Pfeiffer et al, 2001;Utermöhlen et al, 2003;Falcone et al, 2004;McCollister et al, 2007;Utermöhlen et al, 2008;Simonis et al, 2014).…”
Section: Ceramide In Bacterial Infectionsmentioning
confidence: 86%
“…Additional studies showed that infecting mammalian cells with S. aureus, L. monocytogenes, S. typhimurium, E. coli, or pathogenic mycobacteria also activates the acid sphingomyelinase/ceramide system (Esen et al, 2001;Pfeiffer et al, 2001;Utermöhlen et al, 2003;Falcone et al, 2004;McCollister et al, 2007;Utermöhlen et al, 2008). The use of genetically altered cells or pharmacological inhibitors proved the importance of the acid sphingomyelinase/ ceramide system in the infection of mammalian cells by these pathogens.…”
Section: Ceramide In Bacterial Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, when cells are subjected to stress, ASM rapidly translocates from lysosomes to the outer leaflet of the plasma membrane, where it also can hydrolyze sphingomyelin into ceramide [39,40]. This causes reorganization of membrane lipid microdomains, or "raft" structures, and stimulates downstream signaling events.…”
Section: Disease Mechanismmentioning
confidence: 99%
“…1B, after incubation with EDA-SIINFEKL, HEK TLR4 cells presented a higher intensity of fluorescence than HEK LacZ, suggesting that EDA-SIINFEKL is indeed able to bind to TLR4. We also studied the capacity of the EDA-SIINFEKL protein to inhibit the binding of an anti-hTLR4 Ab to HEK-hTLR4 that has been shown to block activation of monocytes with LPS (28). As shown in Fig.…”
Section: Binding Of Eda-siinfekl To Tlr4-expressing Cellsmentioning
confidence: 99%